Institute of Marine Geology and Geophysics - 30 years for studying geology and geophysics in the marine zones of Vietnam and Eastern Sea - Que, Bui Cong (Vietnam Journal of Marine Science and Technology, 2019)
Geological and geophysical investigation and study in the marine zones of Vietnam and Eastern Sea, its application in the mineral exploration, for natural disaster and hazard prevention, environment and resource protection, for sea and island management, marine economic development, sea defence and security is the important, main and long-term tasks of the Institute of Marine Geology and Geophysics. For last 30 years, the institute has a leading role for conducting a numerous projects of national and international programs of marine research and investigation in the marine zones of Vietnam and Eastern Sea. The obtained results and achievements include  big, abundant, up to date databases, newest and detailed schemes and maps, valuable published papers, books, and contributions on characteristics of geophysical fields, deep crustal structure, seabed sediment and environment, geological structure and tectonic evolution, seismotectonics and earthquake, tsunami hazard assessment, mineral potential and perspective evaluation. Results of study on geophysical fields, deep crustal structure, seabed topography and geomorphology have been used for determination of outer limits of continental shelf of Vietnam in the Eastern Sea. Big part of the results was gained from research and investigation projects conducted in the Truong Sa and Hoang Sa areas. On the basis of the obtained achievements, some special tasks are proposed to continue conducting the geological and geophysical research and investigation in the sea of Vietnam and adjacent areas.